A categorisation system for Australia's Integrated Urban Water Management plans. (October 2017) - Guthrie, Lachlan; De Silva, Saman; Furlong, Casey
Abstract: Integrated Urban Water Management plans (IUWM plans) are the processes through which water utilities make and justify important water infrastructure decisions for particular regions. Currently, no widely accepted categorisation system exists, and it is therefore difficult to understand what types of plans exist and the differences among them. This is a barrier to collaboration between agencies, knowledge sharing, and continual improvement of IUWM plan processes. This study has involved in-depth analysis of IUWM plan case-studies to develop and trial a novel IUWM plan categorisation system. This system categorises IUWM plans using six scope descriptors that can shed light on their character and utility. Highlights: Creates a categorisation system for Integrated Urban Water Management plans. Investigation has involved significant industry consultation. Trialled on nine detailed case studies of Integrated Urban Water Management plans. Finds that categorisation systems can assist knowledge sharing.